Study of hepatic involvement in children with dengue infection - Tirumani, Hima Bindu; Bejugam, Vinay Kumar; Naseem, Altaf; Hussain, Arshad; Nizarlalani, . (International Journal of Contemporary Pediatrics, 2017)
Background: Liver dysfunction in children is variable and depends on disease severity. This study was undertaken to identify the range of hepatic involvement in children with dengue infection. Methods: It is a cross sectional observational study conducted in serologically positive dengue fever in children aged between 1-14 years. Hepatic function was studied in all suspected cases over a period of 1 year from June 2015 to June 2016. Results: Out of 55 cases admitted, liver function tests showed AST levels elevated more than 45U/L in 20 (86.9%) DF, 29 (100%) DHF, 3 (100%) DSS patients. ALT levels were elevated more than 45U/L in 16 (69.5%) DF, 24 (82.75%) DHF, 3 (100%) DSS patients. More than 10 fold increase in levels of both AST and ALT was seen in severe dengue. Conclusions: Dengue infection is associated with variable levels of liver dysfunction. The incidence of hepatic dysfunction is more in patients with dengue fever with warning signs and severe dengue. Significant elevation of transaminase levels helps in predicting the occurrence of severe dengue. It is important to be aware of this entity which needs significant attention and management.